The geometry of desert - Kagan, Shelly (New York ; Oxford : Oxford University Press, 2013)
This title explores the hidden complexity of moral desert. Using graphs to illustrate and contrast alternative views, it carefully investigates the various ways in which the value of an outcome varies when people get (or fail to get) what they deserve.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Merit (Ethics)